Mental health care today - Cardoso, Lucilene; Galera, Sueli Aparecida Frari (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to identify the sociodemographic characteristics of caregivers to people who have been discharged from psychiatric hospitalization. A quantitative exploratory study was performed at an outpatient clinic of a mental health service. The sample consisted of patients who had been discharged and their caregivers. A questionnaire was used, and the study was approved by the local research ethics committee. Of the 48 discharged patients, 21 had a caregiver. All the identified caregivers were relatives of the patients, and their average age was 46.6 years. In 38% of cases, the patient's mother was the caregiver. In terms of marital status, 61.9% of the caregivers were married or living in common-law relationships, and only one caregiver did not have children. The main source of income for 28.6% of the participants was temporary keeping eventual jobs. By knowing who is the caregiver of a patient discharged from psychiatric hospitalization it is possible to identify the characteristics that may help to determine the best treatment and professional support for that population.